Innovative low-fat cheese with selenium: Physiological benefits amidst heavy metal exposure - Wahid I. El-Desoki; Ali H.A. Osman; Asmaa H.M. Moneeb; Gamal M. Hamad; Hanan M. Alharbi; Khairiah Mubarak Alwutayd; Taha Mehany (Journal of Agriculture and Food Research)
Selenium (Se) is now recognized as one of the essential trace elements required in the diets of both humans and animals due to its significant physiological effects. This study aims to evaluate the in vivo biological effects of Se-enriched low-fat cheese when administered alongside heavy metals. Initially, rats were exposed to sublethal doses of AlCl3, CdCl2, and Pb acetate (6.11 %, 10.5 %, and 0.5 % of their LD50 values, respectively). Subsequently, the rats were fed either a control diet or Se-enriched low-fat cheese. Results indicated that the weight of groups fed heavy metals in combination with Se-enriched low-fat cheese was significantly higher (P ≤ 0.05) compared to those fed only heavy metals. Rats fed Se-enriched Kareish cheese had significantly lower creatinine and urea levels compared to the control rats, whose values were within the normal range. Additionally, rats consuming Se-enriched low-fat cheese exhibited lower triglyceride levels and reduced organ weights when exposed to heavy metals, suggesting a decrease in their toxicity. In conclusion, Se intake positively influenced the serum lipid profile and lowered the atherogenic index. The findings suggest a potential protective role of Se-enriched cheese in mitigating damage to the liver, kidneys, heart, and other tissues from the negative effects of heavy elements.